2016
DOI: 10.1016/j.neurobiolaging.2016.07.028
|View full text |Cite
|
Sign up to set email alerts
|

TYROBP genetic variants in early-onset Alzheimer's disease

Abstract: We aimed to identify new candidate genes potentially involved in early onset Alzheimer’s disease (EOAD). Exome sequencing was conducted on 45 EOAD patients with either a family history of Alzheimer’s disease (AD, <65 years) or an extremely early age at onset (≤55 years) followed by multiple variant filtering according to different modes of inheritance. We identified 29 candidate genes potentially involved in EOAD, of which the gene TYROBP, previously implicated in AD, was selected for genetic and functional fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 34 publications
0
63
0
Order By: Relevance
“…Unfortunately, patients with NHD usually perish in their 4th to 5th decades of life [67,68]. Recent studies have suggested that heterozygous gene dosage for TREM2 variants that cause NHD in homozygous carriers may confer increased AD risk [43,49,50], and also that rare coding variants of TYROBP may give rise to early-onset AD in an autosomal dominant manner [69].…”
Section: Box 1 Plaque-associated Myeloid Cells: Identity and Impactmentioning
confidence: 99%
“…Unfortunately, patients with NHD usually perish in their 4th to 5th decades of life [67,68]. Recent studies have suggested that heterozygous gene dosage for TREM2 variants that cause NHD in homozygous carriers may confer increased AD risk [43,49,50], and also that rare coding variants of TYROBP may give rise to early-onset AD in an autosomal dominant manner [69].…”
Section: Box 1 Plaque-associated Myeloid Cells: Identity and Impactmentioning
confidence: 99%
“…Furthermore, the clinical features of AD are similar to that of other neurodegenerative diseases, such as FTLD and Parkinson's disease (PD), which might easily lead to misdiagnosis (Piccoli et al, 2016). In the present study, due to the clinical and genetic diversity of AD patients, we screened PSEN1, PSEN2, MAPT, and APP genes in 83 sporadic AD patients, while 53 dementia-related genes which were screened based on previous studies (He et al, 2017;Hooli et al, 2014;Pottier et al, 2016;Vardarajan et al, 2015) and databases such as OMIM (http://www.omim.org/), Orphanet (http://www. orpha.net/consor/cgi-bin/index.php?lng=EN), and HGMD (http:// www.hgmd.cf.ac.uk/ac/index.php) in 25 AD patients with a dementia family history.…”
Section: Introductionmentioning
confidence: 98%
“…Three individuals were found to be carriers of the missense p.Val55Leu. This variant was previously found in a patient with early-onset Alzheimer’s disease also carrying the p.Gly2Glu and to be absent in control population (Pottier et al, 2016). The global allelic frequency of p.Val55Leu in the general population is 0.015, being more frequent in the Asian population.…”
Section: Discussionmentioning
confidence: 55%
“…More recently, an enrichment of TYROBP rare variants was reported in patients with early-onset Alzheimer’s disease (Pottier et al, 2016), and increased mRNA expression levels of TYROBP were found in the brain of LOAD patients (Zhang et al, 2013). …”
Section: Introductionmentioning
confidence: 99%